Allegorical Form and Theory in Hildegard of Bingen’s Books of Visions - Wouters, Dinah. author. aut Link
XI, 291 p.
Keywords: This book analyses how the three books of visions by Hildegard of Bingen use the allegorical vision as a form of knowledge. It describes how the visionary’s use of allegory and allegorical exegesis is linked to theories of cognition, interpretation, and prophecy. It argues that the form of the allegorical vision is not just the product of a medieval symbolic mentality, but specific to Hildegard’s position and the major transformations taking place in the prescholastic intellectual milieu, such as the changing use of Scripture or the shift from traditional hermeneutics to cognitive language philosophy. The book shows that Hildegard uses traditional forms of knowledge – prophecy, the vision, monastic theology, allegorical hermeneutics – in startlingly innovative ways by combining them and by revising them for her own time. Dinah Wouters received her PhD in Latin literature from Ghent University, Belgium. She co-founded the research group RELICS and the openaccess journal JOLCEL, which promotes the study of Latin literature as a European literature. Her current project studies the impact of early modern Latin drama on a European scale.